CONSTRUCT VALIDITY OF THE BATTERY OF DEVELOPMENTAL ASSESSMENT (BDA): A MODEL TOOL FOR LEBANON - Bibi, Huda Husseini (European Scientific Journal, ESJ, 2014)
This study examines the construct validity of the Battery of Developmental Assessment (BDA) - the first comprehensive psycho educational assessment tool designed for students with special Needs in Lebanon and the Arab World. It consists of culture - fair tests, subtests and hands-on activities that help teachers and counselors identify students who are at risk of scholastic delay, and those who perform above average. More importantly, educators would be trained in assessing students, and in proposing suitable individual educational plans. The National Centre for Scientific Research (CNRS) has sponsored the study on construct validity of 27 tests and subtests of the BDA. Findings suggested better solutions for only 6, and items have been revised accordingly. The BDA is now considered a standardized culturally fair assessment tool for differently able students in Lebanon, and other Arab Countries.